Farmers' Water Management Practice and Effective Rainfall and Runoff Ratio of Paddy Fields†. (20th January 2016) - Choi, Dong‐Ho; Jung, Jae‐Woon; Yoon, Kwang‐Sik; Baek, Won‐Jin; Choi, Woo‐Jung
Abstract: Effective rainfall, which is used in paddy fields under farmers' current water management practices, was monitored during the 2008–2012 period in southern Korea. The two paddy fields (HY and JS) studied have an area of 13.69 and 8.06 ha, respectively and are composed of several paddy plots separated by irrigation canals and drains. At the HY site, the effective rainfall ranged from 446 to 794 mm and averaged 567 mm. At the JS site, effective rainfall ranged from 288 to 553 mm and averaged 426 mm. Approximately 64 and 45% of the rainfall for HY and JS, respectively, was used for crop growing in the paddy fields. These amounts were less than the recommended rainwater harvesting criteria in Korea. Since the height of the bund for each paddy plot is approximately 100–300 mm, the plots have sufficient space to hold rainfall; despite this, the field data indicate that rainfall was not used efficiently. This study confirms that farmers have little incentive to use rainfall effectively for rice paddy culture because they can use irrigation water at no charge. Some measures, such as water pricing, incentives for rainwater harvesting, improvement of drainage facilities, and further monitoring of water‐use practices need to be adopted to improve water management efficiency. Copyright © 2016 John Wiley & Sons, Ltd.